'Divine Ulrique': Voltaire and Louisa Ulrica, Princess of Prussia and Queen of Sweden (1751–1771). (1st December 2003) - Rivière, Marc Serge
Voltaire's paradoxical stance towards women is well known. But his relationship with Louisa Ulrica sheds considerable light on his personality and his ability to orchestrate a promotional campaign in Europe. The correspondance and madrigals he addressed to Louisa Ulrica reveal Voltaire's mastery of the art of flattery and his successful quest for yet another royal patron.